Tuning excitability by alloying: the Rh(111)/Ni/H2 + O2 system. Issue 2 (10th December 2015) - Smolinsky, T.; Homann, M.; Imbihl, R.
Abstract : The dynamic behavior of the O2 + H2 reaction on a Rh(111) surface alloyed with Ni has been studied in the 10 −5 mbar range using photoemission electron microscopy (PEEM) as a spatial resolving method. Abstract : The dynamic behavior of the O2 + H2 reaction on a Rh(111) surface alloyed with Ni has been studied in the 10 −5 mbar range using photoemission electron microscopy (PEEM) as a spatial resolving method. For T = 773 K and p (O2 ) = 5 × 10 −5 mbar the bifurcation diagram has been mapped out as a function of the Ni coverage in a range of 0 ML ≤ Θ Ni ≥ 1.3 ML. A critical Ni coverage of Θ Ni, crit = 0.13 monolayers (ML) is required for excitability. In the excitable parameter range pulse trains and irregular chemical wave patterns are found. Whereas the propagation speed of the pulses exhibits no clear-cut dependence on the Ni coverage, the frequency of the local PEEM intensity oscillations increases linearly with Ni coverage in the range from Θ Ni = 0.13 ML to Θ Ni = 1.3 ML.